2021
DOI: 10.17582/journal.aavs/2021/9.8.1259.1266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoke Duration on Compositional Analysis, Deterioration Criteria, Microbial Profile and Sensory Attributes of Marine and Freshwater Fish: A Comparative Study

Abstract: F ish is considered an excellent food of high-quality protein that can replace both red and white meat especially with the fast-growing aquaculture industry in recent years (Kari et al., 2020). It contains both important micro-(minerals and vitamins) and macro-(protein, fat) nutrients. Furthermore, fish contains a high level of polyunsaturated fats (PUFA) which helps in lowering cardiovascular diseases in humans (Mishra, 2020). However, fish is considered a highly perishable food that undergoes many deteriorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The decrease in Enterobacteria numbers in PBE samples may be attributed to various hurdle factors, such as pH reduction, in combination with the bactericidal and antioxidant properties of phenolic compounds present in the smoke, as suggested by Zaki et al (2021). The results indicate the presence of Enterobacteriaceae in the samples but do not provide a comprehensive assessment of their evolution over time.…”
Section: Microbiological Quality Of Smoke-flavored Horse Mackerel Fil...mentioning
confidence: 88%
“…The decrease in Enterobacteria numbers in PBE samples may be attributed to various hurdle factors, such as pH reduction, in combination with the bactericidal and antioxidant properties of phenolic compounds present in the smoke, as suggested by Zaki et al (2021). The results indicate the presence of Enterobacteriaceae in the samples but do not provide a comprehensive assessment of their evolution over time.…”
Section: Microbiological Quality Of Smoke-flavored Horse Mackerel Fil...mentioning
confidence: 88%
“…Furthermore, according to Mendonca et al [54], the values for E. coli expected just after obtaining the final product should be <10 CFU/g and the maximum acceptable value at any point in the shelf life of the food product is 10 3 CFU/g. There have been numerous studies that have indicated that hot smoking showed inhibitory effects against foodborne pathogens such as L. monocytogenes, Aeromonas hydrophila, Yersinia enterocolitica, E. coli, and in other smoked products [7,[55][56][57][58][59].…”
Section: Microbiological Analysismentioning
confidence: 99%